2019
DOI: 10.1021/acs.jpcb.8b10795
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Interactions of 1-Alkyl-3-methylimidazolium Tetrafluoroborate (Alkyl = Octyl, Hexyl, Butyl, and Ethyl) Ionic Liquids with Bovine Serum Albumin: An Alkyl Chain Length-Dependent Study

Abstract: Herein, we have investigated the binding interaction of bovine serum albumin (BSA) with a series of 1-alkyl-3-methylimidazolium tetrafluoroborate (alkyl = ethyl, butyl, hexyl, and octyl) ionic liquids (ILs) in physiological buffer medium. The ILs are chosen basically to understand the effect of alkyl chain length on IL−protein interaction. Experiments have shown that the quenching of fluorescence of BSA is induced by relatively longer alkyl chain-containing ILs, [OMIM][BF 4 ] and [HMIM][BF 4 ]. The enthalpy-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 102 publications
1
51
0
Order By: Relevance
“…Previous studies have investigated the effect of increasing the cation chain length of ILs such as 1-alkyl-3-methylimidazolium chloride on protein stability, as changing the alkyl chain length of the cation (as well as of the anion for other IL families) can directly affect the hydrophobicity of the solvent, and hence the hydrophobic interaction with proteins [ 35 , 36 , 37 , 38 ]. It was reported that increasing the alkyl chain of 25 v / v % alkyl-imidazolium chloride up to hexyl decreased the activity and stability of horseradish peroxidase [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the effect of increasing the cation chain length of ILs such as 1-alkyl-3-methylimidazolium chloride on protein stability, as changing the alkyl chain length of the cation (as well as of the anion for other IL families) can directly affect the hydrophobicity of the solvent, and hence the hydrophobic interaction with proteins [ 35 , 36 , 37 , 38 ]. It was reported that increasing the alkyl chain of 25 v / v % alkyl-imidazolium chloride up to hexyl decreased the activity and stability of horseradish peroxidase [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the peak at ~1710 cm −1 due to the bmim + …COO − (Glu) interaction was observed, for example, in the case of [bmim][SCN]. Islam et al . demonstrated that the secondary structure of BSA remains unaffected in the presence of a shorter alkyl chain length with the ethyl and butyl groups of the 1‐alkyl‐3‐methylimidazolium tetrafluoroborate cation and the longer alkyl chain length of the cation unfolded by BSA.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Islam et al . demonstrated the role of the alkyl chain length of 1‐alkyl‐3‐methylimidazolium tetrafluoroborate during denaturation of bovine serum albumin (BSA). Interestingly, they reported that the alkyl‐chain length of cation in ILs results in the effective IL‐protein interactions.…”
Section: Introductionmentioning
confidence: 99%
“…HSA consists of three homologous uorophores: phenylalanine, tryptophan and tyrosine generally named as domains (I, II and III). 46,47 Among these sites, the main binding sites located in subdomains IIA and IIIA, such as tryptophan (Trp-214) and tyrosine (Tyr-411) residues. 48,49 These residues are found in hydrophobic environment where Tyr residues such as Tyr-263, 319, 332, 334, 341, 353 and 370 are located in domain II of HSA and the location of Trp-214 is shown in Fig.…”
Section: Uv-vis Studiesmentioning
confidence: 99%